Human-Data Interaction in Geoprocessing Applications: Design Implications from the Perspective of Specialists - Capeleti, Bruna Santana; Freire, André Pimenta (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2023: Anais Estendidos do XIX Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi_estendido.2023.229402, 2023)
Data analysis with geoprocessing systems demands apropriate processes to improve the interactive technologies used in these systems, considering user-centered approaches and strategies to reduce the inherent complexity. Another aspect gaining force in the last years is the concept of human-data interaction, which consists of evaluating how users interact with data, not only how the data is presented. This paper aims to provide an analysis of the perspectives of specialists in geoprocessing. It describes the main issues of developing applications focused on geoprocessing and challenges in designing interaction with such systems in four main categories of issues that can influence the production of geographic information products focused on user's needs: technological limitations, closed product scope, low number of specialists in geoprocessing and requirements not focused on geoprocessing. This research aims to integrate the information obtained from this study with a usability evaluation of geoprocessing systems.